Regioselective Glucuronidation of Flavones at C5, C7, and C4' Positions in Human Liver and Intestinal Microsomes: Comparison among Apigenin, Acacetin, and Genkwanin - Hanioka, Nobumitsu; Tanaka-Kagawa, Toshiko; Mori, Yoko; Ikushiro, Shinichi; Jinno, Hideto; Ohkawara, Susumu; Isobe, Takashi (Biological & pharmaceutical bulletin, 2022)
Flavones, which are distributed in a variety of plants and foods in nature, possess significant biological activities, including antitumor and anti-inflammatory effects, and are metabolized into glucuronides by uridine 5'-diphosphate (UDP)-glucuronosyltransferase (UGT) enzymes in humans. In this study, apigenin, acacetin, and genkwanin, flavones having hydroxyl groups at C5, C7, and/or C4'positions were focused on, and the regioselective glucuronidation in human liver and intestinal microsomes was examined. Two glucuronides (namely, AP-7G and AP-4'G for apigenin, AC-5G and AC-7G for acacetin, and GE-5G and GE-4'G for genkwanin) were formed from each flavone by liver and intestinal microsomes, except for only GE-4'G formation from genkwanin by intestinal microsomes. The order of total glucuronidation activities was liver microsomes > intestinal microsomes for apigenin and acacetin, and liver microsomes < intestinal microsomes for genkwanin. The order of CL values (x-intercept) based on v versus V/[S] plots for apigenin glucuronidation was AP-7G > AP-4'G in liver microsomes and AP-7G < AP-4'G in intestinal microsomes. The order of CL values was AC-5G < AC-7G for acacetin and GE-5G < GE-4'G genkwanin glucuronidation in both liver and intestinal microsomes. This suggests that the abilities and roles of UGT enzymes in the glucuronidation of apigenin, acacetin, and genkwanin in humans differ depending on the chemical structure of flavones.